2019
DOI: 10.3390/ma12233825
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-Assisted Synthesis and Characterization of Poly(L-lysine)-Based Polymer/Carbon Quantum Dot Nanomaterials for Biomedical Purposes

Abstract: Carbon nanomaterials in the form of quantum dots have a high potential due to their luminescent properties and low cytotoxicity which allows their use in optical probes for use in bioimaging and biodetection. In this article, we present a novel type of nanomaterials and their obtainment method under microwave-assisted conditions using poly(L-lysine) as a raw material. The ready products were characterized over their chemical structure, pH-dependent fluorescence properties and cytotoxicity on human dermal fibro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(31 citation statements)
references
References 28 publications
(105 reference statements)
3
28
0
Order By: Relevance
“…The presence of hydrophilic groups, such as hydroxyl, carboxyl, and amino groups, is responsible for the excellent water solubility of the prepared CQDs. The results correspond to other researcher's data [6,8,43,44].…”
Section: Scheme 1 Carbon Quantum Dots With the Free Carboxylic Groupsupporting
confidence: 89%
See 4 more Smart Citations
“…The presence of hydrophilic groups, such as hydroxyl, carboxyl, and amino groups, is responsible for the excellent water solubility of the prepared CQDs. The results correspond to other researcher's data [6,8,43,44].…”
Section: Scheme 1 Carbon Quantum Dots With the Free Carboxylic Groupsupporting
confidence: 89%
“…It can be noticed that different carbonizing agents applied for the glucose carbonization ( Table 2) caused diversification in their size and shape. However, their round-shaped morphology is typical for CQDs obtained by the bottom-up approach and corresponds to other researchers' results [36][37][38][39]44]. It can be observed that the Dot-3 sample prepared using tartaric acid is the most uniform one and the average carbon dot diameter is 10 nm.…”
Section: Scheme 1 Carbon Quantum Dots With the Free Carboxylic Groupsupporting
confidence: 87%
See 3 more Smart Citations